Pengaruh Kompetensi Sumber Daya Manusia (SDM) Terhadap Kinerja Karyawan (Studi Kasus di BMT Mitra Rakyat Lamongan) - Ari Nurcahyo Darmawan; Budi Iriani Yudaningrum (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2022)
The purpose of this study was to analyze the influence of human resource competencies to employee performance at BMT Mitra Rakyat Lamongan. The method used in this research is quantitative method by using correlation and regression analysis. The analysis showed that the competence of human resources have a significant effect on the performance of employees, as well as the regression coefficient of human resource competencies which meant that if the competence of human resources increased by one scale, the performance of employees will be increased by zero point nine one assuming factor other Factors unchanged. Thus, human resources competencies at BMT Mitra Rakyat Lamongan make a positive contribution to the performance of the employee.